TINJAUAN HUKUM ISLAM TERHADAP MODEL PROMOSI UMROH SISTEM MEMBER CARD DALAM TRANSAKSI JUAL BELI DI TOKO BUSANA MUSLIM RABBANI JOMBANG - Aulia, Nur; M. Chamim; Afif, abdullah (Irtifaq, 2021)
This article discusses the promotional model at the Rabbani Muslim fashion store in doing its marketing using the member card system. Promotional activities carried out as an effort to maintain and engage with customers to create superior value for the company and customers. In this study, researchers used a qualitative approach. The presence of researchers at the research location is very important because researchers are a key instrument to raise what is in the field. The expressions and actions obtained are primary data sources, while secondary sources are documents through observation, interviews and documentation. Analysis by examining the existing data, carried out by checking the validity of the data. The existence of this Umrah promotion model is one of the strategies to attract consumer interest in making purchases, this is considered effective because member card holders utilize their member cards by making purchases due to price discounts or other special offers from the member. Keywords: Islamic Law, Promotion, Member Card System